Antagonistic Effects of Enrofloxacin on Carbendazim-Induced Developmental Toxicity in Zebrafish Embryos - Ruiqi Fan; Wanjun Zhang; Li Jia; Sunlin Luo; Ying Liu; Yongpeng Jin; Yongchen Li; Xiaoyan Yuan; Yiqiang Chen (Toxics, 2021)
Carbendazim (CAR) and enrofloxacin (ENF) are frequently detected in fruits and meat products, respectively. Since most people consume fruits, vegetables, and meat products, combined exposure is possible, necessitating further evaluation of toxic interactions. In this study, the developmental toxicity of separate and combined exposure was examined in zebrafish embryos. Carbendazim exposure at 0.79 mg/L and above significantly affected developmental parameters, while enrofloxacin alone had no substantial effects on these developmental parameters within the selected concentration range (0.10–0.40 mg/L). Surprisingly, ENF antagonized the CAR-evoked reduction in the 48 hpf (hours post-fertilization) hatching rate and the increases in the 96 hpf malformation and lethality rates. The results revealed that the antagonism might be associated with reciprocal effects of these compounds on metabolism-related genes, such as cyp7a1 and apoa1a. These results reveal a complex interaction between ENF and CAR on metabolic regulation during development and highlight the importance of combined assessment for agents with the potential for simultaneous exposure.